Social media and Web 2.0 for knowledge sharing in product design - Irani, Z.; Sharif, A.; Papadopoulos, T.; Love, Peter (Taylor & Francis, 2017)
© 2017 Informa UK Limited, trading as Taylor & Francis Group. Working collaboratively with internal and external partners (suppliers, customers and internal stakeholders) has been at the epicentre of product design. Knowledge sharing has been well recognised in this context. However, there is limited research that has addressed the role of social media/Web 2.0 in facilitating knowledge sharing for sense- and decision-making within product design. To address this gap, this study draws on the resource-based view (RBV) of the firm and two vignettes that relate to ‘collaborative co-design’ and ‘collaborative design-to-order’. We illustrate the role of social media/Web 2.0 in building knowledge sharing capabilities for sense- and decision-making for internal and external partners during product design. Limitations and further research into the use of social media/Web 2.0 are also discussed.